The Role of Project Health Check Reports in Identifying Indicative Factors of a Troubled Project (Journal of Engineering, 2023)
Government-sponsored projects in Iraq significantly improve the economic situation and provide services but face high rates of troubling blocks. This work aims to identify indicative factors of the Troubled Project using periodic health check reports based on a literature review and interviews with Iraqi experts. As a result, a questionnaire was prepared that included four sections. The first is personal information; the second section is information about knowing the level of institutions’ implementation of project management through prepared documents. The third section is about indicative factors for the project's trouble, including 25 workers; the fourth section is about the questions in the periodic reports to check the project's health. Findings show that the following factors affect the troubled projects: inaccurate initial budget and schedule estimates; poor project scope description; poor team communication; poor planning and definition of the project; lack of a risk management plan and disregarding risk indicators; high rate of rework, and ineffective documentation of project plans with a high relative importance index that ranges from 0.91 to 0.81. Thus, the institutions' activation of the project examination reports with the proposed questions with a relative importance index ranging from 0.88 to 0.77 helps identify the main factors for the troubled projects.